TINJAUAN ETIKA BISNIS ISLAM TERHADAP JUAL BELI PAKAIAN BEKAS IMPOR PADA POTVASHION SIDOARJO - Zhulmi Pradana, Muhammad Asrul; Fikriyah, Khusnul (Universitas Negeri Surabaya, 2023)
Buying and selling is a transaction carried out by two people by exchanging goods for other goods or goods for money. Currently, buying and selling transactions for imported used clothes are mushrooming in Indonesia. The purpose of this study was to determine the application of Islamic business ethics in Potvashion Sidoarjo. This study uses descriptive qualitative research using interview methods (interview). The research results show that buying and selling practices in Potvashion are carried out between sellers and buyers by mutual agreement. Sellers get used clothes through purchases at TP Pagi. Furthermore, before being marketed, the goods are sterilized first. This sale and purchase is reviewed from Islamic business ethics based on existing principles, everything is carried out well and in accordance with the terms and conditions of the sale and purchase and in accordance with Islamic business ethics